Mahiti Shakti - Ravi, Jayanti (2002)
Collectorate of Panchmahals has implemented the Mahitishakti project, which makes available online services, useful public information, exhaustive information on schemes of Government, details of beneficiaries and downloadable forms in about 80 Mahitishakti Kendras spread over the entire district. This has facilitated citizens of a predominantly socio-economically backward district with significant tribal population to access information pertaining to different types of Government to Citizens transactions. Today for a fee of INR 20 (USD 0.50), an online application for National old age pension scheme, change in ration card details, complaints for hand pumps, etc. can be submitted online. Further, the application is processed and the decision is taken without the applicants having to go to the government offices at all. This project essentially leveraged the network of existing STD/PCO (Subscriber Trunk Dialing/Public Call Offices) Centres and dairy centres (Primary milk Co-operatives) without availing subsidy or grants from the government. In fact the government is actively considering the ramping up of the project across the state of Gujarat. - Reproduced.
Keywords: Public administration